Environmental scan of mobile apps for promoting sexual and reproductive health of adolescents in low- and middle-income countries - Aneri Patel; Samantha Louie-Poon; Samar Kauser; Zohra Lassi; Salima Meherali (Frontiers in Public Health, 2022)
BackgroundAdolescence is a period of emotional, mental, and physical change. To increase health seeking behaviors, reduce risky sexual behavior, and improve sexual and reproductive health (SRH) knowledge, adolescents require support and access to SRH services. Providing evidence-informed SRH knowledge to adolescents in low- and middle-income countries (LMICs) can be a challenge as they face unique barriers such as lack of confidentiality, fear of refusal, and stigma from cultural norms. Increasing availability of mobile apps necessitates a comprehensive evaluation of the quality and classification of these SRH mobile applications so that accurate and evidence-based information is reaching its users. Failure to provide SRH services can have damaging effects throughout their development.ObjectiveProvide an overview of current adolescent SRH (ASRH) mobile applications targeting adolescents in LMICs by evaluating their quality and classifying their characteristics.Methods21 search terms related to ASRH mobile apps was developed. These terms were searched in the Apple IOS store and Google Play stores. Inclusion and exclusion criteria were used to screen these apps. Resulting apps were assessed using the Mobile App Rating Scale (MARS) tool. Data extracted was used to rank order each app and identify any gaps in quality.ResultsSearch strategy yielded 2,165 mobile apps. Of these, only 8 were assessed using the MARS tool. Functionality subdomain scored highest at 4.6, while Information scored lowest at 2.5. None of the assessed apps contained information on the MARS items: Evidence base and Goals. Too Shy to Ask had the highest individual app mean score of 4.1, while e-SRHR scored lowest at 2.3.ConclusionsThe goal of this study is to classify and rate the quality of mobile apps designed to promote ASRH behaviors and knowledge in LMICs. Numerous apps were reviewed and all of them failed to provide evidence-based and goal oriented SRH information. Strengths include ease of use, navigation, and gestural designs. Weaknesses include evidence base, goals, willingness to pay, customization, and interactivity. These findings can be potentially used to guide future app development and educate decision makers responsible for policy changes.